2018
DOI: 10.1063/1.5029268
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte complex coacervation by electrostatic dipolar interactions

Abstract: We address complex coacervation, the liquid-liquid phase separation of a solution of oppositely charged polyelectrolyte chains into a polyelectrolyte rich complex coacervate phase and a dilute aqueous phase, based on the general premise of spontaneous formation of polycation-polyanion complexes even in the homogeneous phase. The complexes are treated as flexible chains made of dipolar segments and uniformly charged segments. Using a mean field theory that accounts for the entropy of all dissociated ions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 57 publications
8
107
0
Order By: Relevance
“…36 Finally, a theory by Muthukumar, et al predicts the partitioning of salt to the supernatant phase as well, in this case attributed to the presence of strong, favorable interactions between the dipoles formed between paired complexes and the surrounding salt ions. 135 Experimental and computational efforts further probed the Olvera de la Cruz prediction, 99,100 to demonstrate results consistent with the Sing and Perry observations. One notable example is the work of Li et al; 35 salt was again observed to partition into the supernatant phase, in this case for a different set of coacervate-forming polypeptides (poly(L-lysine) and poly(D,Lglutamic acid)), using thermogravimetric analysis to calculate the coexisting salt and polymer concentrations.…”
Section: Salt Partitioningmentioning
confidence: 61%
See 3 more Smart Citations
“…36 Finally, a theory by Muthukumar, et al predicts the partitioning of salt to the supernatant phase as well, in this case attributed to the presence of strong, favorable interactions between the dipoles formed between paired complexes and the surrounding salt ions. 135 Experimental and computational efforts further probed the Olvera de la Cruz prediction, 99,100 to demonstrate results consistent with the Sing and Perry observations. One notable example is the work of Li et al; 35 salt was again observed to partition into the supernatant phase, in this case for a different set of coacervate-forming polypeptides (poly(L-lysine) and poly(D,Lglutamic acid)), using thermogravimetric analysis to calculate the coexisting salt and polymer concentrations.…”
Section: Salt Partitioningmentioning
confidence: 61%
“…[131][132][133][134] Despite the widespread use of this concept to describe complexation of pair complexes, 29,109 only recently has charge localization been regularly invoked in understanding bulk coacervation. 31,97,135…”
Section: Counterion Releasementioning
confidence: 99%
See 2 more Smart Citations
“…93 This class of models has a number of manifestations, including a semi-phenomenological 'ion equilibrium' model used by Larson and Qin 94 and a ladder conformation-based model developed by Muthukumar. 95 We have recently developed a model inspired by the concept of charge condensation, that we call the transfer matrix (TM) theory of coacervation. [96][97][98][99][100] This theory accounts for the localization of oppositely-charged small molecule ions or polyelectrolytes near a test polyelectrolyte chain, and maps this localization to a 1-D adsorption model.…”
Section: Introductionmentioning
confidence: 99%